Measuring Banking Efficiency in the Pre- and Post-Liberalization Environment : Evidence from the Turkish Banking System - Denizer, Cevdet A. (World Bank, Washington, DC, 2014)
The authors examine banking efficiency before and after liberalization, drawing on Turkey's experience. They also investigate the scale effect on efficiency by type of ownership. Their findings suggest that liberalization programs were followed by an observable decline in efficiency, not an improvement. During the study period Turkish banks did not operate at the optimum scale. Another unexpected result was that efficiency was no different between state-owned and privately owned banks. Banks that were privately owned or foreign owned had been expected to respond better to liberalization, because they were smaller and more dynamically structured, but they were no more efficient than state-owned banks. One reason for the systemwide decline in efficiency might have been the general increase in macroeconomic instability during the period studied.